2011
DOI: 10.1371/journal.pone.0021424
|View full text |Cite
|
Sign up to set email alerts
|

DNA-PK-Dependent RPA2 Hyperphosphorylation Facilitates DNA Repair and Suppresses Sister Chromatid Exchange

Abstract: Hyperphosphorylation of RPA2 at serine 4 and serine 8 (S4, S8) has been used as a marker for activation of the DNA damage response. What types of DNA lesions cause RPA2 hyperphosphorylation, which kinase(s) are responsible for them, and what is the biological outcome of these phosphorylations, however, have not been fully investigated. In this study we demonstrate that RPA2 hyperphosphorylation occurs primarily in response to genotoxic stresses that cause high levels of DNA double-strand breaks (DSBs) and that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
76
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 34 publications
8
76
1
Order By: Relevance
“…Several additional factors may influence RAD51 and DMC1 filament assembly. RPA, for instance, modulates meiotic recombination in yeast (Bartrand et al, 2006;Liaw et al, 2011), and several members for each of the three subunits, one of which is implicated in meiotic DSB repair, are encoded in the genome of Arabidopsis (Shultz et al, 2007;Osman et al, 2009;Sakaguchi (A) Nuclear spreads of PMCs during metaphase I displaying five bivalents in atr rad51 and 10 univalents in atr rad51 asy1 triple mutants. (B) Quantification of meiocytes with univalents, bivalents, or both (irrespective of DNA fragmentation).…”
Section: Discussionmentioning
confidence: 99%
“…Several additional factors may influence RAD51 and DMC1 filament assembly. RPA, for instance, modulates meiotic recombination in yeast (Bartrand et al, 2006;Liaw et al, 2011), and several members for each of the three subunits, one of which is implicated in meiotic DSB repair, are encoded in the genome of Arabidopsis (Shultz et al, 2007;Osman et al, 2009;Sakaguchi (A) Nuclear spreads of PMCs during metaphase I displaying five bivalents in atr rad51 and 10 univalents in atr rad51 asy1 triple mutants. (B) Quantification of meiocytes with univalents, bivalents, or both (irrespective of DNA fragmentation).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we observed a replication protein A 2 hyperphosphorylation pattern after MSI1 overexpression in U251 cells ( Figure 3A) concordant with the induction of DNA damage response in a DNA-PKedependent manner. 22 Most importantly, MSI1 knockdown via siRNA decreased the expression of DNAPKcs in U251 glioblastoma cells ( Figure 3B). Due to the high molecular weight of DNA-PKcs protein (approximately 460 kDa), we used CCCTC-binding factor protein as loading control (83 kDa).…”
Section: Msi1 Targets Dna-pkcsmentioning
confidence: 93%
“…5F) and chromatin binding for RPA phosphorylation. [25][26][27] To determine why RPA phosphorylation is lowered in ZNF668-knockdown cells, we checked the efficiency of RPA recruitment to UV-damaged DNA. Chromatin fractionation revealed that ZNF668-deficient cells had lower levels of chromatin-associated RPA and phosphorylated RPA than control cells (Fig.…”
mentioning
confidence: 99%
“…These data are consistent with previous findings that phosphorylation of S4 and S8 is primarily catalyzed by the DSB-responsive protein DNA-PK. 26 Phosphorylation of RPA at S4 and S8 sites has been implicated in mitotic delay and facilitates DNA DSB repair in response to UV damage. 27 In ZNF668-deficient cells, the impaired RPA phosphorylation and its recruitment to DNA damage sites further support the role of ZNF668 in regulation of RPA activity and DNA damage response.…”
mentioning
confidence: 99%